The role of legitimate politics in addressing the three shortcomings Freedom, Knowledge and Empowerment contained in the Human Development Report 2002 - Amoudi, Fatmeh Jamil (Journal of Humanities & Social Sciences, 2022)
Human development is one of the goals pursued by the policies of the modern state, and this is consistent with the framework of Sharia in making human development one of the purposes of the wise street to create creation and implement the most suitable construction on earth.Human development depends on three pillars: freedom, knowledge, and empowerment. The absence of these three causes society to fall into crises as a result of the generation of their contradictions that obstruct the development process and thus the failure of society to keep pace with the developments of the outside world.The research, through the scientific method based on the collection and analysis of the texts of the Qur’an and the Sunnah of the Prophet, and with the deductive approach, aimed to reach the most important means of Islamic Sharia’s resistance to these shortcomings, considering that they are necessary needs for the development of individuals based on the development of society.Islamic Sharia decided that human development is a necessary interest that achieves a legitimate goal, so it developed scientific and practical approaches that were extracted from the divine approach contained in the Qur’anic stories, and from the prophetic approach contained in the Prophetic Sunnah to fix the defect resulting from it. To adopt and activate them in different eras by preparing centers for the development of human capabilities in accordance with the teachings of Islamic Sharia.
Keywords: Contradictions; freedom; knowledge; empowerment